The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
1988
DOI: 10.1063/1.342133
|View full text |Cite
|
Sign up to set email alerts
|

New, Z-direction anisotropically conductive composites

Abstract: This paper reports the development of a new class of anisotropically conductive materials based on magnetic alignment of conductive particles in nonconductive matrix materials such as elastomeric or adhesive polymers. These composites contain many vertically aligned but laterally isolated chains of ferromagnetic metal spheres, the ends of which protrude from the surfaces for better electrical contact. These novel composite structures exhibit Z-direction-only electrical conduction (>1012 to 1 anisotropy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(15 citation statements)
references
References 0 publications
0
15
0
Order By: Relevance
“…The initial contact resistance was low for all PCB finishes (0.75-1.5 ohms) and it further reduced during 1000 hours of thermal aging, showing good thermal aging performance. 6. The contact resistance of the joints was found to increases with T&H aging.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…The initial contact resistance was low for all PCB finishes (0.75-1.5 ohms) and it further reduced during 1000 hours of thermal aging, showing good thermal aging performance. 6. The contact resistance of the joints was found to increases with T&H aging.…”
Section: Discussionmentioning
confidence: 94%
“…One of the earliest publications that reported on the novel Z-direction conductive adhesive was from AT&T Bell Laboratories [6,7], based on the magnetic alignment of ferromagnetic metal spheres (silver coated nickel) that were dispersed in a non-conductive adhesive polymer. The authors [7] identified that with finer particles, the assemblies' revealed uniformity of resistance values when compared to large particles.…”
Section: Novel Acamentioning
confidence: 99%
“…Ferromagnetic nano-or micro-particles (FMP) dispersed in liquid and subjected to a unidirectional magnetic field can be arranged into various 3D interparticle configurations. [12][13][14] FMP are especially suited for noninvasive tracking and directing labeled cells in vivo 15,16 and have been utilized for tissue engineering approaches, including seeding labeled cells into scaffolds 17 and for ''magnetic force-based cell manipulation'' for the arrangement of cell patterns in sheets for the construction of 3D multilayered tissues. 18,19 This approach has been used to create sheet layers of cells in patterns consisting of various cell types or for forming ring and tubular-like structures in urinary and vascular tissue engineering applications.…”
Section: Introductionmentioning
confidence: 99%
“…Conductive polymers for interconnection (CPI) are prepared from a thin sheet with aligned magnetic particles. CPI has potential applications in device interconnection and circuit testing 14. Sheets of transparent polymer with dispersed and vertically aligned ferromagnetic spheres have been used for touch‐sensitive screens and other visual communication devices 15.…”
Section: Introductionmentioning
confidence: 99%